2008
DOI: 10.1016/s1808-8694(15)30761-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial activity of plants in Acute Otitis Externa

Abstract: Acut e Otitis Externa is an inflammation of the outer auditory meatus, and according to popular saying, medicinal plant extracts can be used in its treatment. Aim: to assess the in vitro antimicrobial activity of the following plants: Aleolanthus suaveolens; Caryophyllus aromaticus; Cymbopogon citratus; Matricaria chamomila; Pithecellobium avaremotemo; Plectranthus amboinicus and Ruta graveolens on the germs that cause otitis externa. Materials and Methods: the minimum inhibitory concentration of extracts and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…In vitro studies showed that M. chamomilla was effective against 25 different gram-positive and gram-negative bacteria and 20 strains of Listeria monocytogenes (5). A study of oral pathogens found on oral biofilm reported that an MTC extract was effective against three strains of Staphylococcus aureus and Candida (21) and that it inhibited growth of Streptococcus mutans and Streptococcus sanguinis, which are important initial colonizers (22). Existing evidence suggests that the antimicrobial effects of MTC are attributable to its terpenic derivatives chamazulene, β-bisabolol, and A and B bisabolol-oxides (23).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that M. chamomilla was effective against 25 different gram-positive and gram-negative bacteria and 20 strains of Listeria monocytogenes (5). A study of oral pathogens found on oral biofilm reported that an MTC extract was effective against three strains of Staphylococcus aureus and Candida (21) and that it inhibited growth of Streptococcus mutans and Streptococcus sanguinis, which are important initial colonizers (22). Existing evidence suggests that the antimicrobial effects of MTC are attributable to its terpenic derivatives chamazulene, β-bisabolol, and A and B bisabolol-oxides (23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in herbal remedies for thousands of years which dates back to ancient Egypt, Greece, and Rome [4, 5]. A diverse range of pharmacological properties have been demonstrated for this plant including anti-inflammatory [6, 7], antimicrobial [8], anticancer [9], analgesic [10], antipruritic [11], antiulcer [12], and acaricidal [13]. These pharmacological properties suggest that the plant might be a valuable therapeutic option for the prophylaxis and treatment of various diseases, including inflammation, ulcers, sedation, hemorrhoids, cough, stomach ache, pharyngitis, and rheumatic pain [14].…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemicals from medicinal plants showing antimicrobial activities have the potential of filling this need, because their structures are different from those of the more studied microbial sources, and therefore their mode of action may too very likely differ (Fabricant and Fansworth 2001). There is growing interest in correlating the phytochemical constituents of a medicinal plant with its pharmacological activity (Prachayasittikul et al 2008;Nogueira et al 2008;Costa et al 2008;Al-Bayati and Al-Mola 2008;Chen et al 2008;Pesewu et al 2008;Turker and Usta 2008). Screening active compounds from plants has lead to the discovery of new medicinal drugs which have efficient protection and treatment roles against various diseases, including cancer (Kumar et al 2004;Sheeja and Kuttan 2007) and Alzheimer's disease (Mukherjee et al 2007).…”
Section: Introductionmentioning
confidence: 99%